Seeds of Cucurbita maxima and Carica papaya are effective for controlling monogeneans in the gills of Leporinus macrocephalus - Luciano Pereira Negreiros; Vitória Moura Carvalho; Tiago Araújo Lima; Eliane Xavier Sousa; Marcos Tavares-Dias (Revista Brasileira de Parasitologia Veterinária, 2022)
Abstract This study was carried out to evaluate the anthelminthic efficacy of seeds of Cucurbita maxima and Carica papaya for controlling monogeneans in the gills of Leporinus macrocephalus, besides hepatosomatic and splenosomatic index and condition factor of host. The fish were fed with seeds of C. maxima or C. papaya for seven days, and these treatments did not cause any mortality among them. Jainus leporini, Urocleidoides paradoxus, Urocleidoides eremitus and Tereancistrum parvus were the monogeneans found, and their prevalence in fish fed with seeds of C. papaya was 100%, while in fish fed with C. maxima the prevalence was 42.8%. Fish fed with seeds of C. papaya showed decreased in intensity and abundance of monogeneans, while fish fed with seeds of C. maxima presented decreased in abundance. Feeding of L. macrocephalus with seeds of C. maxima or C. papaya had efficacy of 69.6 and 67.8%, respectively. The hepatosomatic index of fish fed with seeds of C. maxima or C. papaya was not affected by the treatments. However, the splenosomatic index and condition factor of fish fed with C. maxima seeds decreased. Seeds of C. maxima and C. papaya may be used for controlling monogeneans of L. macrocephalus in fish farming.